Prospek Sistem Pendidikan Islam Di Indonesia - Amanda, Suci Ade; Dewi, Nila Atmasari; Putri, Nabilla (Journal of Sustainable Education, 2025)
This study aims to examine the prospects of the Islamic education system in Indonesia in facing the challenges of the era of globalization and technological development. The main focus of this study is to identify internal strengths and weaknesses, as well as external opportunities and challenges that affect the development of Islamic education in Indonesia. The method used is a descriptive qualitative approach with literature study techniques and in-depth interviews. Data were obtained from various sources such as scientific journals, books, national education policies, and interviews with practitioners and experts in Islamic education. Data analysis was carried out using the SWOT approach to describe the actual situation and future potential of Islamic education. The results of the study show that Islamic education has great potential to develop through strengthening the quality of human resources, modernizing the curriculum, and utilizing digital technology. Although still facing challenges such as limited facilities and quality of teaching staff in several regions, the prospects for the Islamic education system in Indonesia remain bright with government support and increasing public awareness of the importance of education based on Islamic values.